Mechanism of the Anti-Inflammatory Action of 3-(2-Hydroxy-Phenyl)-1-(5-Methyl-Furan 2-y-l) Propenone (HMP). - Liew, Choi Yi (2010)
Chalcones, a subgroup of flavonoids, are found in many plants and many synthetic analogues have been artificially synthesized. Many natural and synthetic chalcones exhibit varying degress of anti-inflammatory activity. In an attempt to discover more potent anti-inflammatory compounds, 3-(2-hydroxyphenyl)-1-(5-methyl-furan-2-y-l) propenone (HMP) was evaluated for its ability to inhibit the synthesis of major proinflammatory mediators and cytokines in interferon-γ (IFN-γ)- and lipopolysaccharide (LPS)-induced RAW 264.7 cells and phorbol myristate acetate (PMA)-differentiated/LPS-induced U937 cells in study I, II, III and IV respectively. The 96-well plate assays included cell viability test, griess, chemical scavenging assay and enzyme-linked immunosorbent assays were conducted meanwhile western blotting, reverse transcription-polymerase chain reactions, immunoprecipitation, kinase assay, electrophoretic mobility shift assay and docking experiment were applied for molecular detection throughout the studies. In study I, II and III, HMP suppressed the production of nitric oxide (NO) at doses as low as 0.78 μM, prostaglandin E2 (PGE2) and interleukin (IL)-1β secretion at doses of 12.5 μM and above meanwhile tumor necrosis factor (TNF)-α and IL-6 secretion at 25 μM with significant inhibitory effects (p < 0.05). HMP did not affect the secretion of chemokines IL-8 and monocyte chemotactic protein-1 (MCP-1) and the anti-inflammatory cytokine IL-10. HMP showed a dose-dependent inhibition of NO synthesis as demonstrated from NO secretion and inducible nitic oxide synthase (iNOS) expression. For study III and IV in which western blotting and kinase assay were conducted, the inhibition of NO synthesis was related to the inhibition of p38 phosphorylation and potent inhibition of p38 kinase activity that led to significant inhibition of phosphorylation of activating transcription factor (ATF)-2. This effect in turn caused significant inhibition of activating protein (AP)-1-DNA binding which partially explains the inhibitory effect upon the synthesis of iNOS. Interestingly, HMP failed to alter phosphorylation of extracellular-signal-related-kinase (ERK) 1/2 and Jun N-terminal kinase (JNK) and did not affect their kinase activity. Furthermore, HMP also failed to inhibit phosphorylation of Inhibitory protein κB (I-κB), nuclear translocation of p65 nuclear factor-κB (NF-κB) and DNA binding of p65 NF-κB. Phosphorylation of signal transducers and activators of transcription (STAT)-1 was also unaffected by HMP. Molecular docking experiments confirmed that HMP fits well in the highly conserved hydrophobic pocket of p38 MAP kinase. In conclusion, in contrast to many anti-inflammatory chalcones, HMP shows a higher selectivity toward NO inhibition therefore providing an interesting drug lead that has potentially less side effects.